Optimización del diseño del componente femoral de una prótesis no convencional bloqueada para cadera - Domínguez Hernández, Víctor Manuel; Rico Martínez, Genaro; Urriolagoitia Calderón, Guillermo (Revista Mexicana de Ingenieria Biomedica, 2004)
Non-conventional prosthesis (NCP) is employed for the proximal end of femur reconstruction after resection of bony tumors of the hip. We developed a novel design of NCP, which the main limitation is its lack of stability. In this work, we determined design parameters that improve its stability, by means of finite element analysis. The model geometry was established by means of tomographic scans practiced to a cadaveric femur. It was developed in seven cases. In the first two cases position of pins with respect to osteotomy site is determined. In the third case length of the stem is analyzed. In the fifth case we studied the effect of external ring, meanwhile the sixth case analyzed the effect of restore abductor lever, and the last one studies three materials commonly used for implants. The design obtained presents proximal pin 50 mm from osteotomy, distal pin from 25 mm from proximal one; stem with a length of 30 cm, the upper end of the femur with the original design; with external ring, and 100% of abductor lever restoration; finally, we chose stainless steel for this implant.